2023
DOI: 10.3390/ijms24076651
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Plumbagin Synergistically Target the PI3K/Akt/mTOR Pathway: A Prospective Role in Cancer Treatment

Abstract: Cancer development is associated with the deregulation of various cell signaling pathways brought on by certain genetic and epigenetic alterations. Therefore, novel therapeutic strategies have been developed to target those pathways. The phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) (PI3K/Akt/mTOR) pathway is one major deregulated pathway in various types of cancer. Several anticancer drug candidates are currently being investigated in preclinical and/or clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Cancer is the second most fatal disease and a major global public health concern 1 . If the current trend continues, it could become the leading cause of mortality in most countries 2 . As per the latest report, the United States of America is expected to experience 1,958,310 new cancer cases and 609,820 cancer deaths in 2023, only 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is the second most fatal disease and a major global public health concern 1 . If the current trend continues, it could become the leading cause of mortality in most countries 2 . As per the latest report, the United States of America is expected to experience 1,958,310 new cancer cases and 609,820 cancer deaths in 2023, only 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Some compounds of natural origin are targets of research and show promising results, such as curcumin, plumbagin and flavopiridol, which are capable of blocking the PI3K/Akt/mTOR pathway, which appears deregulated in different types of cancer. [4,5] Furthermore, there are chemotherapy drugs derived from natural products used in the clinic, such as the alkaloids vinblastine and vincristine, extracted from the species Catharanthus roseus and used in the treatment of cancers such as Hodgkin's lymphoma and Kaposi's sarcoma. Another example is paclitaxel isolated from species of the genus Taxus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments using curcumin and its analogues lead to autophagy in human melanoma cells as they arrest the G2/M phase of the cell cycle [15]. Furthermore, studies have revealed that these compounds decrease mTOR and AKT expression and this concept can be used as a probable target for the treatment of skin cancer [16]. Curcumin analogues explored for treating skin cancer are DMC [17], deketene curcumin [18], diarylpentanoid derivatives of curcumin [19], DM-1 [20], BDMC and 1,7-bis (4hydroxyphenyl)21,4,6-heptatrien-3-one (BHPHTO) [21] (figure 1).…”
Section: Introductionmentioning
confidence: 99%